The Influence of Perfectionism, Role Conflict, Fraud Auditing Training, and Remote Audit on Auditor Performance in Detecting Fraud - Rahman, Rayesh Rasendriya; Irwansyah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
As the content of this research outlines an investigation of how factors such as perfectionism, role conflict, training in fraud auditing, and remote auditing practices influence auditors’ effectiveness in identifying fraud. The growing intricacy of financial activities, along with rapid technological advancements, highlights the need to explore variables that impact auditors' ability to detect fraudulent behavior. A quantitative method was applied through surveys distributed to auditors from the Audit Board of the Republic of Indonesia (BPK) located in Bengkulu Province. The accumulated data were reviewed by Partial Least Squares Structural Equation Modeling (PLS-SEM), selected for its robustness in processing complex frameworks, especially with limited sample units and non-normalized data distributions. Findings indicated that perfectionism, specialized training in fraud detection, and remote auditing contributed positively and significantly to auditors’ performance in fraud detection, whereas role conflict demonstrated a significant negative influence.